CXCL12α/SDF‐1 from perisynaptic Schwann cells promotes regeneration of injured motor axon terminals. Issue 8 (30th May 2017) - Negro, Samuele; Lessi, Francesca; Duregotti, Elisa; Aretini, Paolo; La Ferla, Marco; Franceschi, Sara; Menicagli, Michele; Bergamin, Elisanna; Radice, Egle; Thelen, Marcus; Megighian, Aram; Pirazzini, Marco; et al.
Abstract: The neuromuscular junction has retained through evolution the capacity to regenerate after damage, but little is known on the inter‐cellular signals involved in its functional recovery from trauma, autoimmune attacks, or neurotoxins. We report here that CXCL12α, also abbreviated as stromal‐derived factor‐1 (SDF‐1), is produced specifically by perisynaptic Schwann cells following motor axon terminal degeneration induced by α‐latrotoxin. CXCL12α acts via binding to the neuronal CXCR4 receptor. A CXCL12α‐neutralizing antibody or a specific CXCR4 inhibitor strongly delays recovery from motor neuron degeneration in vivo . Recombinant CXCL12α in vivo accelerates neurotransmission rescue upon damage and very effectively stimulates the axon growth of spinal cord motor neurons in vitro . These findings indicate that the CXCL12α‐CXCR4 axis plays an important role in the regeneration of the neuromuscular junction after motor axon injury. The present results have important implications in the effort to find therapeutics and protocols to improve recovery of function after different forms of motor axon terminal damage. Synopsis: Motor axon terminal degeneration induces perisynaptic Schwann cells to release the chemokine CXCL12α, which binds to neuronal CXCR4 receptors promoting axonal growth to reform a functional neuromuscular junction. The levels of both CXCL12α mRNA and the encoded protein increase in perisynaptic Schwann cells upon nerve terminal degeneration induced by the spider toxin α‐latrotoxin. In vivo neutralization of the chemokine by a specific antibody or inhibition of its receptor CXCR4 delay neuromuscular junction functional recovery after neurodegeneration. In vivo administration of recombinant CXCL12α accelerates neuroregeneration most likely by promoting the growth of motor axons. Abstract : Motor axon terminal degeneration induces perisynaptic Schwann cells to release the chemokine CXCL12, which binds to neuronal CXCR4 receptors promoting axonal growth to reform a functional neuromuscular junction.